Sketching people : an urban sketcher's manual to drawing figures and faces - Chapman, Lynne, 1960- (Barron's Educational Series, Inc., 2016)
"Drawing people in the outside world can be a real thrill; each sketch captures a particular person and place in time. But it can also be a challenge. How do you spot a likely subject? How do you choose the person most likely to stay still? How do you draw movement for the person that refuses to sit still? Sketching People offers straightforward, practical help to give beginning artists the confidence and ability to draw all sorts of people in many different settings."--provided by Amazon.com.